The Caste System in Contemporary Indian Democracy - Zajączkowska, Natalia (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
It is widely acknowledged that Indian society is still significantly plagued, not only by jāti itself, but also omnipresent caste-ridden politics. The aim of this essay is to analyze this social structure in terms of contemporary Indian democracy and explore how it is perceived and evaluated inside of India. I address questions of whether the word democracy is suitable for a country whose society is hierarchically organized, in which the egalitarian tradition remains very limited. This article contributes to the understanding of the coexistence of these seemingly contradicting concepts – Indian caste and democracy. In this article, I elaborate highly influential Dumont’s theory of caste along with two different research studies of Indian scholars. My interpretation is also based on two months of field research during my voluntary work in north-western India in 2016/2017.